Assessment the Effect of Free Trade Agreements on Exports of Lao PDR - VANHNALAT, Bounlert; Kyophilavong, Phouphet -; PHONVISAY, Alay; SENGSOURIVONG, Bouason (International Journal of Economics and Financial Issues, 2015)
This research paper focuses on estimating the impact of Free Trade Agreements (FTAs) between Lao PDR and 32 trading partners. The panel gravity model has been applied over the period of 1996-2011. The overall findings indicate that the preferential utilization is relatively low and is highly concentrated in natural resource products. Since most exporters have difficulty complying with the various local content requirements, the information of preferential utilization is limited, lack of export diversification and the quality of goods cannot meet the standard requirements. The results of the gravity model suggest that a reduction of import tariffs based on WTO commitment has strongly supported trade creation, while several FTAs made with major trading partners are a vital factor to support export growth. The findings suggest Lao’s exports under preferences and GSP treatment would increase trade volume on average by 50% more than those partners who neither have FTAs nor GSP. Keywords: WTO; trade creation; gravity model JEL Classifications: C23; C33; F12; F15